2010
DOI: 10.1093/cvr/cvq362
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase receptor mediates mobilization, migration, and differentiation of mesenchymal stem cells

Abstract: These data suggest a multifaceted function of uPAR in MSC biology contributing to vascular repair. uPAR might guide and control the trafficking of MSCs to the vascular wall in response to injury or ischaemia and their differentiation towards functional VSMCs at the site of arterial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…uPAR function in cell differentiation seems to be of a general nature. As shown previously, uPAR governs VSMC phenotypic modulations from contractile to proinflammatory phenotype and regulates MSC differentiation to VSMC [8,23]. Therefore, a scenario could be suggested that in atherosclerotic vessels uPAR may initiate osteogenic differentiation not only in MSC but in VSMC and most likely in EC as well.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…uPAR function in cell differentiation seems to be of a general nature. As shown previously, uPAR governs VSMC phenotypic modulations from contractile to proinflammatory phenotype and regulates MSC differentiation to VSMC [8,23]. Therefore, a scenario could be suggested that in atherosclerotic vessels uPAR may initiate osteogenic differentiation not only in MSC but in VSMC and most likely in EC as well.…”
Section: Discussionmentioning
confidence: 62%
“…aSMA-positive areas of atherosclerotic plaques examined for C5aR expression in our immunohistological studies may therefore include several lineages, primarily VSMC and MSC. We have reported recently that uPAR deficiency results in a strong inhibition of MSC mobilization from the bone marrow and their engraftment at the site of vascular injury [8]. These abilities of uPAR may additionally contribute to the observed impaired ossification of aortic sinus wall in uPAR -/ -/LDLR -/ -versus uPAR + / + /LDLR -/ -mice.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations